The big bang theory. Holiday collection [videorecording (DVD)]. - Galecki, Johnny; Parsons, Jim, 1973-; Cuoco, Kaley; Helberg, Simon; Bialik, Mayim (Warner Bros Entertainment, 2022)
Jettison the gingerbread. Nix The Nutcracker. Your yuletide just got exponentially funnier! We've gathered 9 beloved holiday-themed episodes of The Big Bang Theory in one prodigious package. Relive all the laughs with Leonard, Sheldon, Penny, Howard, Raj, Bernadette, and Amy as they put their unique spin on the season's festivities. Experience Sheldon's extreme gift protocol. Celebrate Thanksgiving when a mistake from Penny's past comes back to haunt her. Gather with the gang as they contemplate where they'd be if they never met Sheldon. And that's just the start. Sit back and enjoy a new and hilarious holiday tradition with everybody's favorite nerds.